Properties of Wood and Nuts of Makadamia (Macadamia hildebrandii Steen) from Sulawesi - Muhammad Asdar (Buletin Eboni, 2020)
Macadamia hildebrandii Steen is endemic species of Sulawesi. This species is found in the provinces of South Sulawesi, Central Sulawesi and Southeast Sulawesi. Macadamia wood has a distinctive feature that has the prospect of being a raw material for furniture. Meanwhile, the fruit has not been utilized. This paper is a review of wood and macadamia nuts properties that have been studied. The results of these studies show that wood and nuts have the following characteristics: larger rays commonly more than 10 seriate so that it is clearly visible on tangential/flat-sawn boards; classified as strength class III-II; high cellulose contents with alpha cellulose more than 42%; wood calorific value 4,363.5 cal/gr, charcoal calorific value 6868 cal /gr, volatile matter 14.04%, ash 1.36% and fixed carbon 84.60%; durability class IV against soil termites, class II against dry wood termites, and class III-II against decaying fungi; the quality of shaping, turning, boring, and sanding was classified as good (class II), while planing was classified as very good (class I); easily preserved; and easily cracked when dried. Macadamia wood can be used as raw materials for pulp and paper, rayon, charcoal, activated charcoal, light to heavy construction under the roof, furniture, and molding. The use of macadamia wood must consider its low dimensional stability. Macadamia nuts have a fat content of 1.96%, protein 8.38%, carbohydrates 48.44%, starch 46.44%, and tannins up to 8.42%. Proper processing techniques are needed, especially to reduce tannin levels so that macadamia nuts can be consumed.